The political economy of land-water resource governance in the context of food security in Cambodia - Öjendal, J.; Monin, N.; Chanmony, S.; Sidana, B. Z.; Chanrith, N. (Cambodia Development Resource Institute (CDRI), 2023)
Water is central for a variety of livelihoods, development, economic growth, and food production. It is also very important in the large deltas of South and Southeast Asia. Yet, water is turning into a scare resource and global climate change is making its availability more unpredictable. Commercial interests and infrastructure development are also competing for water resources, sometimes at the expense of local smallholders. This report, which is a desk study combined with stakeholder interviews, aims to map out the issues and the previously unknown challenges to efficient water and land management for poverty alleviation and food security. It also serves as a basis for an empirical case study on the same topic. The report illuminates the political economy of land-water resources in the floodplains around the Tonle Sap Lake which constitutes the upper part of the Mekong River Delta and shares seasonal fluctuations and livelihood patterns. The report identifies key challenges for land-water integrity and multi-functionality in food security, nutrition and income impacts for different local producers. The versatile delta landscape and its livelihoods are a complex ecosystem; the driving factors include seasonal water flow variations, the construction of upper Mekong dams, climate change, and the minimal regulations of local resource governance. This evidently makes the governance challenge both immense and urgent. This report maps out opportunities from national to local levels for promoting more systematic, productive and inclusive land-water management. The roles of formal and informal actors within political spaces, their influence on policy and practice, and opportunities to influence these actors are of particular interest. In pursuing the above, the report applies a political economy approach, where the role of the state, its policies and resource allocation are in focus. This also includes the presence of politically and commercially vested interests and how civil society is involved in the general strife for food security and poverty alleviation. The political economy approach constitutes a holistic analysis of how a society is governed and who possesses and utilises which power in order to pursue their interests. At the core of the political economy approach is therefore the illumination of power (and powerlessness) through analysis of actors or a group of actors and their particular interests. The empirical realms in this report focus on contemporary resource management, its institutions and actors.